RELIGIOUS DYNAMICS IN THE G20 AND THE NATIONAL LANDSCAPE: UNVEILING THE INFLUENCE OF ‘ISLAM NUSANTARA’ ON GLOBAL DEVELOPMENT AND HUMANITARIAN INITIATIVES - Arsyad Rizal, Efri; Zuhayda Arsyada, Azma; Pratama, Dito Alif (UIN Raden Mas Said Surakarta, 2024)
Global challenges are becoming increasingly difficult to address, largely due to competition between major world powers and conflicts rooted in identity. These dynamicspose significant risks to peace, security, and well-being both within countries and internationally. This study aims to assess the role of religion in contributing to the development and humanitarian efforts at global and national levels through a qualitative analysis, the study examines the G20 forum, which includes the world’s major economies, to explore how religious influences shape global policies and initiatives. The discussion highlights four key functions of religion: strengthening unity, promoting interfaith dialogue to counter the misuse of religion in politics, opposing wars while supporting victims of conflict, and encouraging ethical behavior to ensure lasting peace.On a national level, with a specific focus on Indonesia, religion has historically served to advance the concept of ‘maslahah’ (the public good) and now holds an increasingly vital role in shaping political systems. Because of upcoming humanitarian missions, this analysis emphasizes the need for spiritual values to be integrated into efforts to enhance global harmony. It also calls for reflection on how effectively these values are being put into practice to support peace and solidarity across nations.